Degradação da amoxicilina em efluentes simulados da indústria farmacêutica via processos oxidativos avançados - Carvalho, Joyce Ferreira de [UNIFESP] (2016)
Among the emerging pollutants, drugs, particularly antibiotics, have attracted great attention. This is due to the high consumption in human and veterinary medicine, the potential of causing toxicity to living organisms and bacterial resistance development, including pathogenic, affecting human health. The main antibiotics dispersion route for the environment is through the aqueous environment, caused by the inefficiency of conventional processes, given to the wastewater from the consumer and producer chain. This work aims to study the advanced oxidation processes such as photolysis, photolysis of hydrogen peroxide, Fenton and photo-Fenton, for the treatment of pharmaceutical industrial wastewater containing amoxicillin. For this, it was used a synthetic wastewater containing amoxycillin (100 mgC L-1). Experiments were performed in a photochemical reactor of bench scale, with annular geometry. Assays were performed the same experimental conditions for comparison and selection of process with improved yield, which was then subjected to the optimization process. The photo-Fenton process had the highest removal rates of organic carbon, mineralizing 58% of the initial organic load in just 30 minutes. The photolysis process of hydrogen peroxide showed the highest percentage of mineralization (97%) of the total reaction time (180 minutes). The photo-Fenton process was optimized by studying the following variables: initial concentration of ferrous ions, molar addition rate of hydrogen peroxide and the interaction of these variables in function of initial degradation rates and organic carbon removal percentage 5, 10, 15 and 30 minutes. Exploratory studies have shown that the variation in initial concentration of ferrous ions (0.03 to 1.00 mmol L-1) did not affect the performance of the photo-Fenton process, it is possible to work with concentrations below the limit established by CONAMA Resolution No. 430 / 2011, eliminating the residual iron removal step. The optimization occurred by Doehlert planning, through which it was possible to evaluate the variables and model the photo-Fenton process based on the responses, with the use of statistical tools. Based on the analysis of variance and response surface methodology, it obtained the rate of addition of hydrogen peroxide as the most influential variable on the initial percentage of organic carbon removal of the photo-Fenton process, and the optimum value of 0.709 mmol L-1 for the initial iron concentrations. The photo-Fenton process was effective in amoxicillin degradation in aqueous solution.